Protective Effect of Polyherbal Composition against Hemorrhagic Shock Condition in an Experimental Rat Model - Vaibhavi, B. Thacker (Asian Journal of Pharmaceutics (AJP), 2021)
Objective: Hemorrhagic shock (HS) is a condition which requires an immediate care and if not treated on time can result in death. Hence, we aim to study the protective role of fixed dose combination of polyherbal composition comprising of an equal amount of aqueous extracts of Azadirachta indica leaves, Carica papaya leaves, and methanolic extract of Andrographis paniculata against fixed volume bleed HS model. Materials and Methods: The study was conducted with 48 male and 48 female Wistar rats divided into 8 groups, normal control (G1), disease control (sublethal and lethal, G2 and G3) and 5 treatment groups (G4–G8). Treatment was initiated on the same day and continued for 14 days. At the end of 14 days, hemorrhage was induced by withdrawing 40% of circulatory blood volume for all groups and 60% of circulatory blood volume for G3. Treatment was continued further for 7 days. Complete blood count, serum levels of glucose, sodium, potassium, and rectal temperature were measured at before, 3 h, 24 h, 72 h, and 7 days post-hemorrhage, whereas interleukin (IL)-6, nuclear factor kappa B (NFƘB), and vasopressin levels were measured at 24 h time point. Serum lactate and bicarbonate levels were measured at 3 h and at the end of the study. Statistical analysis was done using one way ANOVA followed by Dunnett’s test. P < 0.05 was considered statistically significant. Results: At 24 h, glucose levels were high and hematocrit levels were low compared to NC group, which were recovered to normal in all treatment groups at the end of the experiment except in disease control group. Our findings were further supported by serum level of electrolytes as well as IL-6, NF-ƘB, and vasopressin levels which were elevated in response to HS condition at 24 h posthemorrhage. We have seen significant (P < 0.0001, P < 0.001, P < 0.01, P < 0.05) changes in the level of these parameters in disease control group compared to other groups. Recovery at the end of the experiment indicates that animals have responded to our treatments with maximum effect has been seen in G7 group. Conclusion: The polyherbal extracts used in this experiment have the potential to be used alone or in combination with available conventional medical therapy against HS condition to provide symptomatic relief, to improve quality of life and to promote the survival.